MANAGEMENT OF INTERNAL HEMORRHOID WITH RUBBER BAND LIGATION PROCEDURE - Winangun, I Made Arya; Tusta Adiputra, Putu Anda; Maliawan, Sri; Kawiyana, Ketut Siki (E-Jurnal Medika Udayana; vol 2 no 10 (2013):e-jurnal medika udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Hemorrhoid is regarded as the cases most seen in population. The prevalence of this cases about 4,4% with the incidence 12 of 1.000 patient. The current management of hemorrhoid is lifestyle modification, conservative management such as farmacology, minimally invasive treatment and more aggressive therapy using surgical procedure. Rubber band ligation was one of the minimally invasive procedures. This procedure was easy, inexpensive, and can be done outpatient using simple tools without complicated procedure like hemorrhoidectomy. Some studies explained rubber band ligation effectively done in internal hemorrhoid grade II and grade III even this procedure still had minimal complication such as bleeding and unpleasentness /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: hemorrhoid, rubber band ligation